Can We Talk About Transparency in Moroccan Public Finances? - Taouab, Omar; Ameur, Sara (European Scientific Journal, ESJ, 2018)
The link between good governance and better economic and social outcomes is increasingly acknowledged. Transparency – openness about policy objectives, preparation and application – is a key element of good governance. Availability of reliable, relevant and timely information about the public finances allows the government and the citizens to see clearer. Upgraded public service delivery, including the providing of education, healthcare and sanitation, depends on the transparent and efficient management of public funds. Many nations still face challenges in the effective management of their financial resources. Therefore, Transparency is considered as an income to strengthening governance. For more than a decade, civil society organizations around the world, as well as international financial institutions, have been pushing governments to provide the public with more comprehensive budget information. The movement for greater public finance transparency has been gaining momentum in recent years; the recent global financial crisis has put even more emphasis on the importance of budget transparency. Calls for transparency, accountability, and equality have emerged in the whole world, especially the Arab world, with citizens summoning their governments to reveal their incomes and expenditures, as well as strategies and ambitions. To contribute to these efforts, we will be studying and analyzing the reference tools proposed by the international organizations for measuring the degree of budget transparency, and we will attempt to examine the finance transparency in Morocco.